The role of rurality in the experience of persistent poverty in Scotland. - Stevelink, Sharon; Wilson, Graeme (International Journal of Population Data Science, 2025)
Objectives We know that the longer someone lives in poverty, the more harmful this is. Yet, little is known about the trends and patterns of persistent poverty and what role the level of rurality may play in the experience of persistent poverty. Methods Data from Understanding Society were used to estimate persistent poverty rates in Scotland, defined as living in a household with annual income below 60% of the annual UK median in at least three years out of four. The Scottish Government six- and threefold urban/rural classification was used to explore the impact of rurality on the experience of persistent poverty. Results For the period between 2018 and 2022, one in 10 people in Scotland were in persistent poverty and this trend has been relatively stable over time. Rates of persistent poverty are comparable across children, pensioners and working-age adults. Work is on-going how these rates vary across different geographical areas and what type of households are at risk of experiencing persistent poverty. Conclusion Policy should consider localised patterns of poverty to target effective mitigation of poverty drivers, using interventions both to support people to escape persistent poverty and to prevent people from experiencing poverty in the first place.